PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN LAJU REAKSI DI KELAS XI MIA SMA NEGERI 2 PEKANBARU - Safna Nur Afiana; R.Usman Rery; Johni Azmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aimed to increase students outcomes implementation of contextual teaching and learning (CTL) on the reaction rates in XI MIA SMAN 2 Pekanbaru. The type of this research is experimental research with randomized control group pretest-posttest design. Subject of this research are XI MIA 1 as the experimental class, XI MIA 2 as the control class which were determined randomly after conducting normality and homogeneity test. The experimental group was treated with implementation of contextual teaching and learning (CTL) while the control group without implementation of contextual teaching and learning (CTL) The data analysis to test the hypothesis was using t-test right side. Based on the data analysis, it is obtaine tcount = 4,74 and ttable = 1,67 with α=0,05, dk = 70, tcount > ttable is 4,74 > 1,67, It’s mean implementation of contextual teaching and learning (CTL) can improve students outcomes on the reaction rates in XI MIA SMA Negeri 2 Pekanbaru. The influence implementation learning model contextual teaching and learning (CTL) to improvement of the student outcomesas high as 24,3%.Keywords: Contextual Teaching and Learning (CTL), Learning Outcomes.